Biological agents of bioterrorism - preparedness is vital - Janoutová, J; Filipčíková, R; Bílek, K; Janout, V (Epidemiologie, mikrobiologie, imunologie, 2020)
Bioterrorist threats and attacks are still an issue of concern in the world. Biological agents are divided into three categories. The highest priority agents classified in category A pose a massive risk to public health and national security. The society should be prepared for this risk. Health professionals in the Czech Republic should be aware of the diseases caused by category A agents, which are not common in the country. In this context, the project of the Ministry of the Interior of the Czech Republic “Decontamination of the injured persons” has been implemented at the Faculty of Health Sciences, Palacký University, Olomouc. The article provides an overview of selected serious infectious risks and information on the project the aim of which is to create certified methodical procedures and guidelines on situations related to bioterrorism.
Keywords: anthrax; bioterorismus; ebola; Plague; tularemie; pravé neštovice; Bioterrorism; lidé; decontamination; tularemia; Tularemia; antrax; botulism; Anthrax; variola; Czech Republic; Civil Defense; plague; civilní obrana; Česká republika; Smallpox; bioterrorism; mor; Humans